FIGURATIVE LANGUAGE IN FIVE SONGS OF JUSTIN BIEBER - Suryani, Jellin (ID Solutions, 2023)
Abstract— The goal of this study is to analyze the different figurative language styles present in Justin Bieber's album songs. The type of figurative language and the type of meaning of the data from Justin Bieber's songs were defined by the researcher using the descriptive qualitative method. The purpose of this study was to identify the many types of figurative language that may be heard in Justin Bieber's songs. The purpose of this study was to identify the many types of figurative language that may be heard in Justin Bieber's songs. There are two issues with the study's research namely (1) what are the types of figurative language that found in song lyrics of Justin Bieber’s songs? (2) What is the meaning of each type of figurative language? In this study, two theories were employed: the first is that put forth by Perrine (1974), and the second is that of Leech (1981). In this study, the researcher identified three categories of figurative language: similes (3), metaphors (1), and hyperbole (4). In conclusion, it is evident that hyperbole is the most common sort of figurative language used in Justin Bieber's songs.